Studies on Antimicrobial and Antifungal Activities of Ziziphus mauritiana Against Human Clinical Bacterial and Fungal Pathogens: Antimicrobial and Antifungal Activities of Z. mauritiana - Amin, Adnan; Shah, Swahid; Andaleeb, Saadia; Khan, Muhammad Mohibullah; Khan, Muhammad Ayaz (Biological Sciences - PJSIR, 2012)